Medicine and Society, New Perspectives in Continental Philosophy - Meacham, Darian (Springer, 2015)
This volume addresses some of the most prominent questions in contemporary bioethics and philosophy of medicine: ‘liberal’ eugenics, enhancement, the normal and the pathological, the classification of mental illness, the relation between genetics, disease and the political sphere, the experience of illness and disability, and the sense of the subject of bioethical inquiry itself. All of these issues are addressed from a “continental” perspective, drawing on a rich tradition of inquiry into these questions in the fields of phenomenology, philosophical hermeneutics, French epistemology, critical theory and post-structuralism. At the same time, the contributions engage with the Anglo-American debate, resulting in a fruitful and constructive conversation that not only shows the depth and breadth of continental perspectives in bioethics and medicine, but also opens new avenues of discussion and exploration.